Fabrication of a Multifunctional Nano‐in‐micro Drug Delivery Platform by Microfluidic Templated Encapsulation of Porous Silicon in Polymer Matrix. (16th April 2014) - Zhang, Hongbo; Liu, Dongfei; Shahbazi, Mohammad‐Ali; Mäkilä, Ermei; Herranz‐Blanco, Bárbara; Salonen, Jarno; Hirvonen, Jouni; Santos, Hélder A.
<x xml:space="preserve">Abstract</x> A multifunctional nano‐in‐micro drug delivery platform is developed by conjugating the porous silicon nanoparticles with mucoadhesive polymers and subsequent encapsulation into a pH‐responsive polymer using microfluidics. The multistage platform shows monodisperse size distribution and pH‐responsive payload release, and the released nanoparticles are mucoadhesive. Moreover, this platform is capable of simultaneously loading and releasing multidrugs with distinct properties. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>